Identifying and ranking the effective financial factors on rural entrepreneurial small businesses - Khosro Farahi; Parvaneh Gelard; Hamid Tohidi (International Journal of Research in Industrial Engineering)
Rural entrepreneurship is one of the most important goals of policy-makers to develop villages and prevent migration from rural to urban areas. Significant challenges at the rural entrepreneurship level have reduced the entrepreneurship development process. Recognizing these challenges can be constructive in identifying the various dimensions related to rural entrepreneurship and removing barriers to rural business development. This study aims to identify the effective financial factors on entrepreneurship in rural small businesses and rank these factors. The research method applied based on purpose and data collection is a semi-structured interview done through interviews with academic experts, implementers of rural employment and entrepreneurship projects, and entrepreneurs. Data analysis and validation of financial factors on rural entrepreneurship in both service and agriculture sectors were performed using the fitting of a time-series regression model. The results indicate a positive and significant effect of rural population ratio, financing through financial institutions, economic growth, openness rate in business space, gender composition, and inflation rate in agriculture sectors, as well as a significant reverse effect of official employment rate, job-seeking population ratio, exchange rate uncertainty, government employment rate and graduation ratio on entrepreneurship in both service and agriculture sectors. Finally, the results of the Friedman test showed that the financing factor through financial institutions has the highest average rating due to the bank-oriented financial resources of entrepreneurial enterprises in the rural service and agriculture sectors. Therefore, policy-makers seeking to develop rural entrepreneurship should prioritize policies related to the ease of access of rural businesses to financial resources.